Mutation of the glycine residue preceding the sixth tyrosine of the LAT adaptor severely alters T cell development and activation - Arbulo-Echevarria, Mikel M.; Vico-Barranco, Inmaculada; Zhang, Fanghui; Fernandez-Aguilar, Luis M.; Chotomska, Martyna; Narbona-Sánchez, Isaac; Zhang, Lichen; Malissen, Bernard; Liang, Yinming; Aguado, Enrique (Frontiers in Immunology, 2022)
The LAT transmembrane adaptor is essential to transduce intracellular signals triggered by the TCR. Phosphorylation of its four C-terminal tyrosine residues (136, 175, 195, and 235 in mouse LAT) recruits several proteins resulting in the assembly of the LAT signalosome. Among those tyrosine residues, the one found at position 136 of mouse LAT plays a critical role for T cell development and activation. The kinetics of phosphorylation of this residue is delayed as compared to the three other C-terminal tyrosines due to a conserved glycine residue found at position 135. Mutation of this glycine into an aspartate residue (denoted LATG135D) increased TCR signaling and altered antigen recognition in human Jurkat T cells and ex vivo mouse T cells. Here, using a strain of LATG135D knockin mice, we showed that the LATG135D mutation modifies thymic development, causing an increase in the percentage of CD4+CD8+ double-positive cells, and a reduction in the percentage of CD4+ and CD8+ single-positive cells. Interestingly, the LATG135D mutation alters thymic development even in a heterozygous state. In the periphery, the LATG135D mutation reduces the percentage of CD8+ T cells and results in a small increment of γδ T cells. Remarkably, the LATG135D mutation dramatically increases the percentage of central memory CD8+ T cells. Finally, analysis of the proliferation and activation of T lymphocytes shows increased responses of T cells from mutant mice. Altogether, our results reinforce the view that the residue preceding Tyr136 of LAT constitutes a crucial checkpoint in T cell development and activation.